NegotiAct: Introducing a Comprehensive Coding Scheme to Capture Temporal Interaction Patterns in Negotiations - Jäckel, Elisabeth; Zerres, Alfred; Hemshorn de Sanchez, Clara S.; Lehmann-Willenbrock, Nale; Hüffmeier, Joachim (Group & organization management, 2024)
In the present research, we developed NegotiAct, a comprehensive coding scheme for negotiations, comprising 47 mutually exclusive behavioral codes. NegotiAct was derived by systematically integrating (i) 89 extant coding schemes for negotiations, (ii) pertinent findings from negotiation research, and (iii) specific interaction behaviors that were previously not considered in coding schemes for negotiations (e.g., active listening). To facilitate the application of NegotiAct, we designed a coding manual with precise instructions and with definitions and examples for every code. NegotiAct can be customized to address many research questions in experimental settings as well as field research by splitting codes into more specific behaviors. Thereby, differentiated codes can always be traced back to the original codes, preserving comparability across studies and facilitating cumulative research. In combination with interaction analytical methods, NegotiAct enables scholars to detect and investigate specific communication patterns across the negotiation process. As a first empirical validation of NegotiAct, we demonstrate a substantial interrater reliability for 18 videotaped negotiations (κ = .80) and conduct an exploratory validation analysis, studying the relation of multi-issue offers, active listening, and joint gains.